First crystal structures of oxo-bridged [CrIIITaV] dinuclear complexes: spectroscopic, magnetic and theoretical investigations of the Cr–O–Ta core. (1st June 2018) - Androš Dubraja, Lidija; Jurić, Marijana; Lafargue-Dit-Hauret, William; Pajić, Damir; Zorko, Andrej; Ozarowski, Andrew; Rocquefelte, Xavier
Abstract : The vibrational, electronic, structural and magnetic properties of dinuclear compounds with a Cr–O–Ta bridge were validated with DFT calculations. Abstract : Heterodinuclear complexes [Cr(bpy)2 (H2 O)(μ-O)Ta(C2 O4 )3 ]2 ·3.5H2 O (1 ) and [H2 (terpy)][Cr(terpy)(C2 O4 )(μ-O)Ta(C2 O4 )3 ]·0.5H2 C2 O4 ·2.5H2 O (2 ) (bpy = 2, 2′-bipyridine; terpy = 2, 2′:6′, 2′′-terpyridine) have been synthesised through a reaction of a tris(oxalate)oxotantalate(v ) anion and a complex chromium(iii ) cation with corresponding aromatic N-donor ligands. These are the first examples of a Cr–O–Ta bridge in molecular compounds, and the first report of heterodinuclear complexes prepared from a tris(oxalate)oxotantalate(v ) anion as a building block. Structural analysis of both compounds revealed that Ta V in pentagonal bipyramid geometry is connected through a slightly bent μ-O bridge to Cr III having a distorted octahedral environment. The geometry optimization performed with density functional theory (DFT) calculations gave very good agreement with the experimentally obtained structure of1 . Room temperature solid state UV-Vis spectra were recorded for both compounds and compared to those of starting reagents, in order to test for possible new electronic transitions attributed to the metal-to-metal charge transfer between Cr III and Ta V through the oxo-bridge. Infrared (IR) spectroscopy supported with DFT calculations was used to assign vibrational modes to all spectral features, especially those coming from the molecular μ-oxo bridge. Temperature dependence of magnetic properties of1 and2 were probed with magnetic susceptibility measurements on a SQUID magnetometer. Additionally, zero-field splitting parameters were determined from electron paramagnetic resonance (EPR) spectra of compound1 and experimentally obtained values were confirmed by DFT calculations.